A rare case of metachronous penile and urethral metastases from a rectal mucinous adenocarcinoma. (5th November 2015) - Christodoulidou, Michelle; Sahdev, Varun; Muneer, Asif; Nigam, Raj
Abstract : Metastatic lesions in the penis are uncommon in patients with prostate or bladder cancer but penile metastatic lesions from rectal tumours are rare with only 65 cases reported in the literature. We describe the case of a 70-year-old man who developed metastatic lesions within his corpus cavernosum 2 years after being diagnosed and treated for a mucinous adenocarcinoma of the rectum and a year after a wedge resection of an isolated lung metastasis. He proceeded with total penectomy and intraoperatively two skip lesions were also found within the wall of his urethra; histological analysis proved that these were also metastatic lesions. A perineal urethrostomy was formed with the remaining macroscopically healthy urethra. He made a good recovery from his operation and continued his treatment under the oncology team.